Efektivitas Program Pekarangan Pangan Lestari Terhadap Ketahanan Pangan dan Pembangunan Berkelanjutan Rumah Tangga di Kota Pekanbaru - Hilmadhia Marwah; Irdayanti Irdayanti (Yayasan Almanar Pujud, 2026)
This study aims to analyze the effectiveness of the Sustainable Food Yard Program implemented by the Food Security Agency of Pekanbaru City in maintaining household food security. The research background highlights Pekanbaru’s high dependence on food supplies from outside regions and the increasing vulnerability of low-income households to food access. A qualitative approach was applied, using interviews, documentation, and observations with program beneficiaries, particularly Women Farmer Groups. The findings reveal that the P2L program has not significantly improved local food availability but has contributed to social empowerment and economic aspects by supporting the fulfillment of households’ daily food needs. The main challenges include limited productive land, low community participation, and issues of funding sustainability and technical assistance. Thus, the effectiveness of P2L is more evident in social empowerment and household food fulfillment, while its contribution to strengthening local food security remains limited.